Pengaruh Pemanfaatan Koleksi Fiksi di Kantor Perpustakaan dan Arsip Kabupaten Padang Pariaman - Mestika, Tresia; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This research aims to describe (1) the effect of fiction in the current collections of Library and Archives Pariaman District (2) obstacles encountered in the use of fiction in the collection of Library and Archives Office of Padang Pariaman district. The writing is done through direct observation in the field. From the observation it can be concluded that the activity utilization fiction collection at Library and Archives Office is influenced by two factors: internal and external. Constraints faced in the utilization fiction collection is that visitors do not find the language standard, visitors do not find the desired fiction books. Here it can be suggested that in order to improve the utilization of a collection of fiction needed a good cooperation between visitors and librarians. Keywords: fiction collection